SCHIZOTHORAX EURYSTOMUS (SCHIZOTHORAX EURYSTOMUS) WHICH IS DISTRIBUTED IN SHAHRIKHONSOY SOME MORPHOBIOLOGICAL INDICATORS (Scientific journal of the Fergana State University, 2024)
The article presents the results The article presents information on the morphobiological indicators of blackfish caught from the Shahrikhonsoy main canal flowing through the Fergana valley. The morphometric and reproductive characteristics of this fish species were analyzed.